2008
DOI: 10.1002/mrc.2194
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR assignments of three nitrogen containing compounds from the mangrove endophytic fungus (ZZF08)

Abstract: A new natural product, named phomopsin A, 1-(meta-hydroxyphenyl)-4-hydroxy-3-isoquinolone (1), together with two known compounds cytochalasin H (2) and glucosylceramide (3), was isolated from the mangrove endophytic fungus Phomopsis sp. (ZZF08) obtained from the South China Sea coast. The structures were elucidated by 1D and 2D NMR experiments including COSY, HMQC, and HMBC. According to NMR and single-crystal X-ray diffraction, it was found that some assignments about (1)H and (13)C NMR data for cytochalasin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…Column chromatography and preparative HPLC were used to isolate the six known compounds: cytochalasin J ( 1 ), cytochalasin H ( 2 ) [10,11,12], 5'-epialtenuene ( 3 ) [13,14], alternariol monomethyl ether (AME) ( 4 ) alternariol (AOH) ( 5 ) [15,16,17], cytosporone C ( 6 ) [18,19], and the new natural product 2-hydroxyalternariol ( 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Column chromatography and preparative HPLC were used to isolate the six known compounds: cytochalasin J ( 1 ), cytochalasin H ( 2 ) [10,11,12], 5'-epialtenuene ( 3 ) [13,14], alternariol monomethyl ether (AME) ( 4 ) alternariol (AOH) ( 5 ) [15,16,17], cytosporone C ( 6 ) [18,19], and the new natural product 2-hydroxyalternariol ( 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further known cytochalasans were isolated from other species of Sordariomycetes and identified by comparing the 1 H and 13 C chemical shifts and the HRMS data to those reported previously ([25] for 6 ; [26] for 7 , [27] for 8 ; [28] for 1 0 , [21] for 11 – 13 , [27] for 15 – 18 ). However, upon comparison of our NMR data with those published previously [26,27] for l -696,474 ( 7 ) and 21- O -deacetyl- l -696,474 ( 8 ), respectively, it was found that 1 H and 13 C assignments for methyl groups CH 3 -22 and CH 3 -23 were different to those in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds isolated from active extracts included eight well‐known cytochalasins ( 1–8 ) (Fig. ), which were identified from several endophytic fungi and some terrestrial filamentous fungi.…”
Section: Resultsmentioning
confidence: 99%